The Construction of Automotive Media Multi-Brand Matrix and Brand Synergy Strategy - Yuan, Dingyi; Fu, Shuai; Yin, Liang (International Journal of Global Economics and Management, 2024)
This paper delves into the establishment of a multi-brand matrix within the automotive media sector and its pivotal role in advancing brand synergy strategy. The construction of a multi-brand matrix enables enterprises to foster complementarity and collaboration among various brands, facilitating resource sharing and leveraging complementary advantages, thereby elevating the competitiveness and overall influence of the entire conglomerate. Concurrently, the brand synergy strategy exerts a reciprocal impact on the development of the multi-brand matrix, contributing to its refinement and optimization. Moreover, the paper conducts an analysis of the challenges inherent in the interactive relationship and proposes corresponding coping strategies to address these obstacles.In essence, the interplay between the automotive media multi-brand matrix and brand synergy strategy holds profound significance for the industry's growth and progression. By aligning the strategic interdependence of multiple brands and optimizing collaborative potential, companies can effectively navigate the complexities of the contemporary market landscape and position themselves for sustained success in an increasingly competitive environment. This dynamic interrelationship underscores the importance of cohesive and synergistic approaches in driving the industry forward, ultimately paving the way for enhanced innovation, market penetration, and sustained growth within the automotive media domain.